Unleashing your inner leader : an executive coach tells all - Bevenour, Vickie (John Wiley & Sons, Inc., 2015)
This book presents the premise that there is a powerful leader inside each of us. The focus is on real life exercises and case studies to help you discover, release, and leverage your inner leader to reach heights in your career that you never thought possible. It discusses the individual's impact on the organization and which professional behaviors most frequently demonstrate leadership competencies. Conduct a forensic intervention to find out what is going awry in your professional development, or what has gone wrong in the past, and craft a strategy to overcome obstacles, gain unmistakable clarity about yourself, and focus your abilities to match organizational needs. It will help you recognize where you fall on the leadership spectrum, and provides practical advice for shaping your brand of leadership to capitalize on your authentic capability and potential. --